(untitled) (diségno, 2018)
All of our activities of Surveying, Documenting, Analyzing, Interpreting, Planning, Communicating necessarily converge or rotate around the ‘representation model’, whether it be of ‘restitution’ (from a survey), of ‘reconstruction’ (of a non-existing reality and/or design aims) or of prediction (restoration, project). Survey is the full expression of disciplinary specificity and autonomy, as regards methods and techniques, but still an integral part of the more complex process of “historical-critical analysis.” An analysis that must lead to an integral and integrated knowledge of the architectural specifics, of the clustered buildings, or of the urban reality subject to observation, and to the expression of a “value assessment” in relation to aesthetic and historical instances [Brandi 1977].